Mosques in the Metropolis: Incivility, Caste, and Contention in Europe - Becker, Elisabeth (University of Chicago Press, 2021)
Intro -- Contents -- Preface: Spirit Meeting Stone -- 1. The European Metropolis: Where Doors and Walls Meet -- 2. Caste, or the Order of Things Defied -- 3. Kaaba in Papier-Mâché: Inside the Sehitlik Mosque -- 4. Ordinary Angels: Sehitlik Mosque and the Metropolis -- 5. Messianic Horizon: Inside the East London Mosque -- 6. Hope, Interrupted: The East London Mosque and the Metropolis -- 7. Unsettled Europe: On the Threshold of Remembrance -- Afterword: The Memory of Trees -- Acknowledgments -- Notes -- Bibliography -- Index.